Development of in vitro germination and cryopreservation protocols of pollen in wild Lathyrus species to overcome longevity and asynchronous flowering constraints - Rinky Resma Panda; Padmavati G. Gore; Aishmita Gantait; Esha Singh; Mahesh Rao; S. Rajkumar; Shiv Kumar; Kuldeep Tripathi; Sandhya Gupta (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Unveiling the secret lives of endemic plants and understanding exclusive species of Gujarat, India through ecological niche modelling - Pankajkumar C. Prajapati; G. Sandhya Kiran; Agradeep Mohanta; Kavi K. Oza; Shrishti Rajput (Plant Ecology, 2026)

Homocysteine as a Dual Vasculo-Metabolic Risk Factor for Cognitive Impairment Specific to the Indian Context: A Systematic Review and Meta-Analysis - G. Sandhya; Mrinalini Rajashekhar; Thomas Gregor Issac (Indian Journal of Clinical Biochemistry, 2026)

Hacking heterocysts: advances in the genetic regulation of heterocyst differentiation - Sandhya Deora; G. S. Deora; Subhasha Nigam; Harish (Archives of Microbiology, 2026)

Delving into the BURP Super family: A Comprehensive QTL-Assisted Study on RD22 genes and its Role in Salinity Stress Tolerance in Chickpea - Sandhya Tripathi; Chellapilla Bharadwaj; Maloti Hembram; Neeraj Kumar; Aravind K. Konda; B. Mondal; N. C. Gupta; G. P. Dixit; K. R. Soren (Biochemical Genetics, 2025)

Tree‐Ring Inferred Seven Century Long Snowfall Record From the Cold‐Arid Western Himalaya, India - Krishna G. Misra; Vikram Singh; Ram R. Yadav; Sandhya Misra (International Journal of Climatology, 2025)
In the present study, Himalayan cedar samples from eight climate‐stressed sites were collected and used to examine the snowfall variability over the Lahaul‐Spiti region. The tree‐growth and climate relationship was explored using response function analysis, which revealed a positive tree‐growth relationship with precipitation and a negative relationship with temperature. The response function analysis also suggested that cool and moist climatic conditions favour tree growth, while warm and dry conditions reduce tree radial growth over the Lahaul‐Spiti region. Taking this relationship as a guide, we further tested the relationship of tree‐ring chronologies with observational Snow Water Equivalent (SWE) data. An observed statistically significant positive correlation encouraged us to develop the linear regression model for reconstruction. The linear regression models were used to develop a new November to April SWE record for the cold‐arid Lahaul‐Spiti region, Himachal Pradesh. The SWE reconstruction extends back to AD 1290 and revealed low SWE values in the year 1626 (223.6 mm), 1970 (254.4 mm), 1329 (270.1 mm), 1705 (271.9 mm), 2008 (278.5 mm), and high SWE values in the year 1306 (791.7 mm), 1348 (771.0 mm), 1412 (769.7 mm), 1569 (769.1 mm) and 1661 (765.9 mm). The reconstructed SWE is consistent with available precipitation, drought, and river flow records developed from different regions of the western Himalaya, underpinning its importance in understanding the regional hydro‐climatic variability. The cross‐field correlation analysis of the present SWE record with gridded precipitation, PDSI, and MADA also revealed a significant correlation for the westerly dominated Himalayan regions. The positive spatial correlation of SWE with snow cover area of the Northern Hemisphere further endorses the strength of our reconstruction. We also noted strong linkages of SWE with the El‐Niño Southern Oscillation in the present study, while the dominance of the Indo‐Pacific climate system is observed in the spectral analysis. Therefore, we believe that our attempt to develop a seven‐century‐long SWE record from a data‐scarce Himalayan region will strengthen our understanding of the hydrological variations in the long‐term perspective.

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

On the role of Sri Lankan land mass in safeguarding the southeastern coast of India from Southern Ocean swell attacks - K G Sandhya; R Harikumar; P A Francis; Balaji Baduru; T M Balakrishnan Nair (Journal of Earth System Science, 2025)

Recent Development in Nanoparticle-Assisted Microbial Fuel Cell for Enhanced Reduction of Chromium - G. Vijay Samuel; Nibedita Dey; R. Govindarajan; Kuppusamy Sathishkumar; Muthusamy Govarthanan; J. Sakthidasan; J. Sandhya; Lakshmi Sundeep (Current Microbiology, 2024)

Micro-Raman Spectroscopy Explains the Population-Scale Heterogeneity in Lipid Profile in Chlamydomonas reinhardtii Cultivated Under Single-Stage and Two-Stage Salt Stress - Shubhangi Pandey; Sandhya Mishra; G. Archana; Debjani Bagchi (BioEnergy Research, 2024)

A systematic appraisal of ecological niche modelling in the context of phytodiversity conservation - G. Sandhya Kiran; Pankajkumar C. Prajapati; Agradeep Mohanta (Environment, Development and Sustainability, 2024)

Spectral mixture analysis of AVIRIS-NG data for grouping plant functional types - Ramandeep Kaur M. Malhi; G. Sandhya Kiran; Prashant K. Srivastava; Bimal K. Bhattacharya; Agradeep Mohanta (Advances in Space Research, 2024)

Efficient extraction and analysis of precious metals with a conducting polymer modified magnetic sorbent material - Abiral Poudel; Sandhya Adhikari; Timnit Y. Asfaha; Joseph G. Lawrence; Manjula M. Kandage; Michal Marszewski; Jon R. Kirchhoff (Resources, Conservation and Recycling, 2023)

Genomic survey of high-throughput RNA-Seq data implicates involvement of long intergenic non-coding RNAs (lincRNAs) in cytoplasmic male-sterility and fertility restoration in pigeon pea - Swati Saxena; Antara Das; Tanvi Kaila; G. Ramakrishna; Sandhya Sharma; Kishor Gaikwad (Genes & Genomics, 2023)

Defect-induced electronic modification and surface reconstruction of catalysts during water oxidation process - Gracita M. Tomboc; Sandhya Venkateshalu; Quang-Tung Ngo; Songa Choi; Bruno G. Pollet; Hangil Lee; Kwangyeol Lee (Chemical Engineering Journal, 2023)

Population genetic research on the Spadenose shark, Scoliodon laticaudus (Chondrichthyes, Carcharhinidae), reveals the presence of two significantly differentiated clades along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; P. U. Zacharia; Shoba J. Kizhakudan; K. V. Akhilesh; Sujitha Thomas; Subal Kumar Roul; M. Muktha; Swati Priyanka Sen; G. B. Purushottama; Shikha Rahangdale; K. K. Bineesh; et al. (Marine Biodiversity, 2023)

Exome sequencing and microarray identified a novel large exonic deletion in SYT2 gene in an ultra-rare case with recessive CMS type 7 - C. P. Ravi Kumar; Parag M. Tamhankar; Radhika Manohar; Sheetal Sharda; G. K. Madhavilatha; S. G. Thenral; Sandhya Nair; A. K. Bojamma (Journal of Genetics, 2022)

Evaluation of the Bioefficacy and Insecticide Compatibility of Entomopathogens for Management of Whitefly (Hemiptera: Aleyrodidae) on Upland Cotton Under Laboratory and Polyhouse Conditions - Satish Kumar Sain; Dilip Monga; Sandhya Kranthi; Neelakanth S. Hiremani; Dipak T. Nagrale; Rishi Kumar; Surender Kumar Verma; Yenumula G. Prasad (Neotropical Entomology, 2022)

A comprehensive review on leguminous galactomannans: structural analysis, functional properties, biosynthesis process and industrial applications - Priya Sharma; Sandhya Sharma; G. Ramakrishna; Harsha Srivastava; Kishor Gaikwad (Critical Reviews in Food Science and Nutrition, 2022)

Comparative transcriptome analyses revealed different heat stress responses in pigeonpea (Cajanus cajan) and its crop wild relatives - G. Ramakrishna; Parampreet Kaur; Anupam Singh; Sunishtha S. Yadav; Sandhya Sharma; N. K. Singh; Kishor Gaikwad (Plant Cell Reports, 2021)

Population genetic structure of the oceanic whitetip shark, Carcharhinus longimanus, along the Indian coast - S. Sreelekshmi; Sandhya Sukumaran; T. G. Kishor; Wilson Sebastian; A. Gopalakrishnan (Marine Biodiversity, 2020)

Synergetic use of in situ and hyperspectral data for mapping species diversity and above ground biomass in Shoolpaneshwar Wildlife Sanctuary, Gujarat - Ramandeep Kaur M. Malhi; Akash Anand; Ashwini N. Mudaliar; Prem C. Pandey; Prashant K. Srivastava; G. Sandhya Kiran (Tropical Ecology, 2020)

Comparative RNA editing profile of mitochondrial transcripts in cytoplasmic male sterile and fertile pigeonpea reveal significant changes at the protein level - Tanvi Kaila; Swati Saxena; G. Ramakrishna; Anshika Tyagi; Kishor U. Tribhuvan; Harsha Srivastava; Sandhya; Ashok Chaudhury; Nagendra Kumar Singh; Kishor Gaikwad (Molecular Biology Reports, 2019)

A climatological study of the spatio-temporal variability of land surface temperature and vegetation cover of Vadodara district of Gujarat using satellite data - Neha Nandkeolyar; G. Sandhya Kiran (International Journal of Remote Sensing, 2019)

Spectral Modelling on the Characteristics of High Frequency Tail in Shallow Water Wave Spectra at Coastal Puducherry, East Coast of India - P. A. Umesh; Prasad K. Bhaskaran; K. G. Sandhya; T. M. Balakrishnan Nair (Pure and Applied Geophysics, 2019)

Event-Related Potentials in Response to Facial Affect Recognition in Patients with Schizophrenia - G. Sandhya; H. P. Prakash; K. R Nayak; R. V. Behere; P. R. Bhandary; A. S. Chinmay (Neurophysiology, 2019)

High Frequency Tail Characteristics in the Coastal Waters off Gopalpur, Northwest Bay of Bengal: A Nearshore Modelling Study - P. A. Umesh; Prasad K. Bhaskaran; K. G. Sandhya; T. M. Balakrishnan Nair (Pure and Applied Geophysics, 2018)

Status, Prospects, Threats, and the Way Forward for Sustainable Management and Enhancement of the Tropical Indian Reservoir Fisheries: An Overview - U. K. Sarkar; K. M. Sandhya; P. Mishal; G. Karnatak; S. Kumari; P. Panikkar; R. Palaniswamy; M. Karthikeyan; S. Sibina Mol; T. T. Paul; V. L. Ramya; D. S. K. Rao; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

Analysis of SARAL/AltiKa Wind and Wave over Indian Ocean and its Real-time Application in Wave Forecasting System at ISRO - Suchandra Aich Bhowmick; Ruchi Modi; K. G. Sandhya; M. Seemanth; T. M. Balakrishnan Nair; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

Estimation of variables explaining urbanization concomitant with land-use change: a spatial approach - G. Sandhya Kiran; Usha B. Joshi (International Journal of Remote Sensing, 2013)

Interaction of fishes with pathogenic micro-organisms and application of phages for their control: a review - Swapnil G. Sanmukh; Dilip B. Meshram; Waman N. Paunikar; Sandhya Swaminathan (Reviews in Fish Biology and Fisheries, 2012)

Cloning and characterization of truncated cry1Ab gene from a new indigenous isolate of Bacillus thuringiensis - Sandhya Darsi; G. Divya Prakash; V. Udayasuriyan (Biotechnology Letters, 2010)

Recombinant TCR Ligand Reverses Clinical Signs and CNS Damage of EAE Induced by Recombinant Human MOG - Sushmita Sinha; Sandhya Subramanian; Ashley Emerson-Webber; Maren Lindner; Gregory G. Burrows; Marjorie Grafe; Christopher Linington; Arthur A. Vandenbark; Claude C. A. Bernard; Halina Offner (Journal of Neuroimmune Pharmacology, 2010)

Lysophosphatidylcholine induces inflammatory activation of human coronary artery smooth muscle cells - Nambi Aiyar; Jyoti Disa; Zhaohui Ao; Haisong Ju; Sandhya Nerurkar; Robert N. Willette; Colin H. Macphee; Douglas G. Johns; Stephen A. Douglas (Molecular and Cellular Biochemistry, 2007)

Forest change detection in Kalarani round, Vadodara, Gujarat— a Remote Sensing and GIS approach - Jessica P Karia; M C Porwal; P S Roy; G Sandhya (Journal of the Indian Society of Remote Sensing, 2001)